APLIKASI ASUHAN KESEHATAN GIGI DAN MULUT PADA KELUARGA BAPAK I WY. S DENGAN ANAK MENDERITA KARIES GIGI DI WILAYAH KERJA PUSKESMAS DENPASAR SELATAN TAHUN 2023 - I Gede Surya Kencana; Ida Ayu Dewi Kumala Ratih (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2023)
Â Bali Province is one of the provinces that has a high caries occurrence rate 41,6%. Based on the result of basic health research, the prevalence of caries, especially in Badung Regency, can be seen from the caries index (DMF-T),namely 11.10% with a value of D (Decay), 17.40% M (Missing) and 7.43% with F (Filling). The purpose of this study was to determine the degree of dental and oral health in families and to assist families in solving problems related to dental and oral health maintenance. This research method is action research with the stages of assesment, diagnostik, family care plan, implementation and ecvaluaion. On the physical examination, the clients dental and oral hygiene dta, OHI-S 1.00, is in good category, caries experience is measured by DMF-T: 2.00 and the condition of the periodontal tissue is measured by CPITN with an averege healthy sextan of 60%. Conclusion; the risk of developing caries regarding enamel in MD.A. is related to the inability and lack of knowledge of the family in caring for family members who experience toothache. The problem is partially resolved because the family says there is still material that is not understood, namely about the consequences of caries on the teeth.